Redox-Robust Pentamethylferrocene Polymers and Supramolecular Polymers, and Controlled Self-Assembly of Pentamethylferricenium Polymer-Embedded Ag, AgI, and Au Nanoparticles - Gu, Haibin; Ciganda, Roberto; Castel, Patricia; Vax, Amelie; Gregurec, Danijela; Irigoyen, Joseba; Moya, Sergio; Salmon, Lionel; Zhao, Pengxiang; Ruiz, Jaime; Hernandez, Ricardo; Astruc, Didier (Chemistry - A European Journal, 2015)
We report the first pentamethylferrocene (PMF) polymers and the redox chemistry of their robust polycationic pentamethylferricenium (PMFium) analogues. The PMF polymers were synthesized by ring-opening metathesis polymerization (ROMP) of a PMF-containing norbornene derivative by using the third-generation Grubbs ruthenium metathesis catalyst. Cyclic voltammetry studies allowed us to determine confidently the number of monomer units in the polymers through the Bard-Anson method. Stoichiometric oxidation by using ferricenium hexafluorophosphate quantitatively and instantaneously provided fully stable (even in aerobic solutions) blue d5 FeIII metallopolymers. Alternatively, oxidation of the PMF-containing polymers was conducted by reactions with AgI or AuIII, to give PMFium polymer-embedded Ag and Au nanoparticles (NPs). In the presence of I2, oxidation by using AgI gave polymer-embedded Ag/AgI NPs and AgNPs at the surface of AgI NPs. Oxidation by using AuIII also produced an AuI intermediate that was trapped and characterized. Engineered single-electron transfer reactions of these redox-robust nanomaterial precursors appear to be a new way to control their formation, size, and environment in a supramolecular way.
CRIS-Team Scopus Importer:2020-10-13
Keywords: cyclic voltammetry; metallopolymers; nanoparticles; pentamethylferrocene; ring-opening-metathesis polymerization